Case Report: Effective and Safe Treatment With Certolizumab Pegol in Pregnant Patients With Cogan’s Syndrome: A Report of Three Pregnancies in Two Patients - Venhoff, Nils; Thiel, Jens; Schramm, Markus A.; Jandova, Ilona; Voll, Reinhard E.; Glaser, Cornelia (Frontiers in Immunology, 2021)
Cogan’s syndrome is a rare autoimmune disease characterized by ocular inflammation and audiovestibular manifestations. Treatment consists of systemic glucocorticoids and other immunosuppressive agents including methotrexate, cyclophosphamide and TNF-α-inhibitors. Due to potential ovarian or fetal toxicity immunosuppressive treatment options are limited during pregnancies. Thus far there is a paucity of reports on pregnancies in Cogan’s syndrome. With minimal transplacental transfer, Certolizumab pegol is considered to be safe for the use in pregnant patients with underlying inflammatory diseases. However, there is no literature on the use of TNF-α-inhibitors in Cogan’s syndrome in general and especially during gestation. Here we report three pregnancies in two Cogan’s Syndrome-patients treated with Certolizumab pegol. Treatment with Certolizumab pegol was effective and well tolerated in patients with Cogan’s syndrome and seems to be a safe treatment option during pregnancy.